Use of interactive performance optimization for identifying the ideal profile of swine finishing producers - LUIZ F. SANGOI; ALEXANDRE M. KESSLER; JULIO C. M. SILUK; ANDREA M. L. RIBEIRO; ALVARO L. NEUENFELDT JÚNIOR (Engenharia Agrícola, 2015)
The present research aimed to develop a modeling capable of identifying the ideal profile of swine finishing producers using the interactive performance optimization, which began by verifying qualitative the criteria considered most relevant to the decision-making, generating a closed structured diagnosis that covers the socioeconomic aspects about the activity, until the design of a mathematical model able to translate the data obtained in quantitative information. For the verification, it was proposed a practical study for a universe of 120 members of a cooperative in the state of Rio Grande do Sul, Brazil. The results showed that, from the application and the definition of the ideal profile, it was possible to verify that 82 producers are in the group of those who have obtained a "Good" performance, and to 44 the result is in the range between 86% to 90% from the ideal, which means that most have short or medium-term conditions to evolve their status for the considered "Very Good", where only 12.5% of the producers are currently.